2017
DOI: 10.1002/pros.23432
|View full text |Cite
|
Sign up to set email alerts
|

PSCA promotes prostate cancer proliferation and cell‐cycle progression by up‐regulating c‐Myc

Abstract: PSCA is a novel cell cycle regulator with a key role in mediating c-Myc-induced proliferation. PSCA may be a potential diagnostic marker and therapeutic target for patients with PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…The data from Taeb et al show that expression of PSCA increased from benign prostate tissues (BPH) and HGPIN to prostate cancer and that its expression in prostate cancer was positively associated with poor cell differentiation in Iran [ 30 ]. Similar to these results, our previous studies also revealed that PSCA can promote prostate cancer proliferation and cell-cycle progression and can increase the metastatic potentials by EMT in prostate cell lines [ 15 , 31 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The data from Taeb et al show that expression of PSCA increased from benign prostate tissues (BPH) and HGPIN to prostate cancer and that its expression in prostate cancer was positively associated with poor cell differentiation in Iran [ 30 ]. Similar to these results, our previous studies also revealed that PSCA can promote prostate cancer proliferation and cell-cycle progression and can increase the metastatic potentials by EMT in prostate cell lines [ 15 , 31 ].…”
Section: Discussionsupporting
confidence: 88%
“…Shorter OS was also found in patients with intensive expression of PSCA. As shown in some previous studies, PSCA can promote prostate cancer cell proliferation and escalate the distant metastasis of prostate cancer [ 15 , 31 ]. Therefore, PSCA may play a carcinogenesis role in the progression of prostate cancer, and its expression level in prostate cancer sections might be a useful parameter for judging the prognosis of patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…c-Myc plays an important role in regulating cell proliferation, differentiation, and apoptosis [ 4 ]. Li et al revealed that the PI3K/AKT signaling pathway was involved in PSCA-promoted cell proliferation and cell cycle progression by upregulating c-Myc in prostate cancer [ 17 ]. Moreover, the previous work demonstrated that c-Myc functions in pancreatic cancer as a central oncogene [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Semaphorin 7A (SEMA7A), a GPI-AP, has been found to promote EGFR-tyrosine kinase inhibitor (TKI) resistance in EGFR-mutated lung cancer through activating the mTOR pathway [6]. Prostate stem cell antigen (PSCA), another type of GPI-AP, has been indicated to play an important role in tumorigenesis, proliferation and cell cycle progression via the upregulation of c-Myc expression [7]. In addition, alkaline phosphatase (ALP), glypican-3 (GPC3), and carcinoembryonic antigen (CEA) have been identified as biomarkers of cancers [810].…”
Section: Introductionmentioning
confidence: 99%